PERGESERAN BUDAYA KOMUNIKASI DI ERA MEDIA BARU (STUDI KASUS PENGGUNAAN LAPOR OLEH MASYARAKAT KOTA SOLOK) - Meynalti Handhayani; Ernita Arif; Rahmi Surya Dewi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
As a new medium, the Lapor application has a platform that can have implications for the culture of communication of its users. Users of the Report application can easily provide their aspirations and complaints and get the clear information needed. This research uses a qualitative approach with descriptive methods. The technique used in data collection uses observation, interviews and documentation. The theory used is symbolic interaction theory and cultural norm theory. Where the theory of symbolic interaction states that humans interact with each other and act on the meaning that is obtained from the results of social interactions conducted with others, namely by using the media report to get the desired information. Meanwhile, according to the theory of cultural norms, the Report media used by users gives new impressions and beliefs to users of the Report application and can change the prevailing norms and create a new culture of communication using the Report application.